Resonance Micro-Weighing of Sub-Picogram Mass with the Use of Adaptive Interferometer - Romashko Roman; Efimov Timofey; Kulchin Yuri (Measurement Science Review, 2014)
Mass of macroscopic object is easily measured by a suitable balance. However, this approach becomes inapplicable if mass of microscopic object is to be determined. Alternative approach for mass measurement is based on using the micromechanical resonator as an inertial balance where oscillation frequency is shifted by small quantities of adsorbed mass. In this work we present experimental results of applying an adaptive interferometry technique based on dynamic hologram recorded in photorefractive CdTe crystal for measuring picogram mass adsorbed on micromechanical resonators with dimensions 215×40×15 μm3. It is also shown that the resonance micro-weighing system based on adaptive interferometer has potential for reducing the threshold of mass detection down to 10-17 g in the case of using a resonator with sub-micron dimensions